Chronic and acute effects of walnuts on antioxidant capacity and nutritional status in humans: a randomized, cross-over pilot study. - McKay, Diane L.; Chen, C-Y Oliver.; Yeum, Kyung-Jin.; Matthan, Nirupa R.; Lichtenstein, Alice H.; Blumberg, Jeffrey B. (2016)
Background: Compared with other common plant foods, walnuts (Juglans regia) are consistently ranked among the highest in antioxidant capacity. In vitro, walnut polyphenols inhibit plasma and LDL oxidation, while in animal models they lower biomarkers of oxidative stress and raise antioxidant capacity. A limited number of human feeding trials indicate that walnuts improve some measures of antioxidant status, but not others.; Keywords: red blood cell, low density lipoprotein, polyunsaturated fatty acids, Oxygen Radical Absorbance Capacity, ORAC with protein precipitation by perchloric acid, Ferric Reducing Antioxidant Power, Total Antioxidant Performance, Total Radical-trapping Antioxidant Parameter, Trolox Equivalent Antioxidant Capacity, cardiovascular disease, body mass index, electrocardiogram, daily value, malondialdehyde, pyridoxal phosphate, glutathione peroxidase, high density lipoprotein, ethylenediaminetetraacetic acid, butylated hydroxytoluene, red blood cells, 2,2-azobis(2-amidopropane) hydrochloride, Trolox equivalents, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene, thiobarbituric acid, high pressure liquid chromatography, gallic acid equivalents, standard deviation, Food and Drug Administration, alpha, beta, gamma.; Springer Open.